1)x^1/3(x-x^2/3) Attempt:- (x^1/3 * x)-(x^1/3 * x^2/3) =x^2/3-x 2) a^-1/4(a^3/8+a^3/2) Attempt:- answer is 2a Are both of these attempts correct and please explain in steps if they are wrong (Thank you,)
Follow Math Help Forum on Facebook and Google+
Originally Posted by mj.alawami 1)x^1/3(x-x^2/3) Attempt:- (x^1/3 * x)-(x^1/3 * x^2/3) =x^2/3-x note that x^(1/3) * x = x^(4/3) 2) a^-1/4(a^3/8+a^3/2) Attempt:- answer is 2a a^(-1/4) * a^(3/8) + a^(-1/4) * a^(3/2) = a^(1/8) + a^(5/4) fixed
View Tag Cloud